Visualisation of image restoration for Indonesian public officials during the Covid-19 Pandemic - Pratiwi, Miftha; Andarini, , Rindang Senja; Setiyowati, Rini; Santoso, Anang Dwi (Faculty of Communications Science, Dr. Soetomo University, 2022)
Most studies on image restoration concentrate on text analysis of firms and CEOs in the Western context; hence, there is a need to explore similar practices in public organisations or public officials in an Eastern context. This study intends to investigate tactics and methods for repairing the image of public officials in eastern nations, including Indonesia, to fill this void. Visual and thematic analysis was performed on a dataset containing 2,000 Instagram posts from seven public officials in Indonesia. According to our findings, the visual analysis identifies six content kinds, while the thematic analysis identifies ten content types. They constitute image restoration methods, such as compensation, bolstering, corrective action, and shifting the blame, and image recovery strategies, such as reducing offensiveness of event, corrective action, and denial. This study reveals that, contrary to western literature, public authorities in Indonesia tend to employ the method of minimising the offensiveness of an occurrence.